1976
DOI: 10.1038/bjc.1976.2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous shedding and antibody induced modulation of histocompatibility antigens on murine lymphomata: Correlation with metastatic capacity

Abstract: Summary.-The lability of cell surface histocompatibility antigens of 2 murine lymphomata was examined. These 2 tumours differ greatly in their capacity to metastasize in syngeneic hosts. Cells of the metastatic lymphoma released histocompatibility antigens in vivo and in vitro at a greater rate than cells of the nonmetastasizing lymphoma. Antigen/antibody complexes formed by the addition of allo-antiserum to intact cells disappeared more rapidly from the surface of cells of the metastatic line. We propose that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…The highly invasive and meta static ESb subline of a murine T lymphoma [69] adheres to syngeneic hepatocytes and lung tissue in vitro, whereas the parent Eb lymphoma, which has low invasive and met astatic potential, does not [70]. We found that the ESb T lymphoma cells had a stronger expression of Tn and T on their outer plasma membranes than did Eb [50,65].…”
Section: T and Tn In Cancer Cell Adhesion To Hepatocytesmentioning
confidence: 99%
“…The highly invasive and meta static ESb subline of a murine T lymphoma [69] adheres to syngeneic hepatocytes and lung tissue in vitro, whereas the parent Eb lymphoma, which has low invasive and met astatic potential, does not [70]. We found that the ESb T lymphoma cells had a stronger expression of Tn and T on their outer plasma membranes than did Eb [50,65].…”
Section: T and Tn In Cancer Cell Adhesion To Hepatocytesmentioning
confidence: 99%
“…These pan-CA auto-antigens [8][9][10] play a profound role in cancer pathogenesis. 11) Specific adhesion between invasive, metastatic murine Esb T-lymphoma cells and syngeneic hepatocytes has been demonstrated 12,13) ; direct molecular binding of the Esb cells, which were later confirmed to strongly express T and Tn antigens on their cell surfaces, 14) to the corresponding ligands was the first step after the recognition of hepatocyte ligands. Moreover, cultured breast CA DU4475 cells and desialylated, isologous erythrocytes [TRBC] bound specifically to the Gal/GalNAc receptors of rat Kupffer cells and of hepatocytes.…”
mentioning
confidence: 99%
“…Tumour factors such as phenotypic diversity (Weinhold et al, 1979), tumour invasive factors (e.g. collagenase) (Woolley, 1982;Pauli et al, 1983), antigen shedding (Davey et al, 1976), and immunosuppressive factors (Eccles & Alexander, 1975), may be involved when growth resumes.…”
mentioning
confidence: 99%